2005
DOI: 10.1016/j.ijgo.2005.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and neonatal effects of forceps versus vacuum operative vaginal delivery

Abstract: The purpose of this study was to assess the differences in immediate maternal and neonatal morbidity of vacuum and forceps assisted deliveries.A retrospective analysis of parturients files with singleton vertex presentation who underwent an instrumental delivery during a period of 40 months was performed. The rate of forceps delivery versus vacuum extraction in Wolfson Medical Center is approximately 1:6. In order to obtain a meaningful and capable number of instrumental deliveries for assessment, all vacuum d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 5 publications
3
3
0
4
Order By: Relevance
“…16 Currently there is tendency to rely on vacuum extraction which may be because of recent evidence of decreased maternal trauma with vacuum extraction compared to forceps deliveries in randomized trials and by a substantial improvement in the technique of vacuum extraction, especially in the material used for vacuum cups. 17 In our study we also found the ratio of 1/6 between forceps and vacuum application, which is in accordance with findings derived from Lurie S et al 18 In our study 74% of forceps delivery and 58% of ventouse deliveries were carried out in primigravida, which is in accordance with prior study done by Akhtar S. 19 For vacuum delivery, common indications were to cut short the second stage of labour (42.85%) followed by prolonged second stage of labour (25.7%), poor maternal efforts (14.3%) and fetal distress (12.9%). For forceps delivery main indication was to cut short the second stage of labour (41.2%) followed by fetal distress (32.9%).…”
Section: Discussionsupporting
confidence: 93%
“…16 Currently there is tendency to rely on vacuum extraction which may be because of recent evidence of decreased maternal trauma with vacuum extraction compared to forceps deliveries in randomized trials and by a substantial improvement in the technique of vacuum extraction, especially in the material used for vacuum cups. 17 In our study we also found the ratio of 1/6 between forceps and vacuum application, which is in accordance with findings derived from Lurie S et al 18 In our study 74% of forceps delivery and 58% of ventouse deliveries were carried out in primigravida, which is in accordance with prior study done by Akhtar S. 19 For vacuum delivery, common indications were to cut short the second stage of labour (42.85%) followed by prolonged second stage of labour (25.7%), poor maternal efforts (14.3%) and fetal distress (12.9%). For forceps delivery main indication was to cut short the second stage of labour (41.2%) followed by fetal distress (32.9%).…”
Section: Discussionsupporting
confidence: 93%
“…In our series, maternal traumatic complications related to forceps use were dominated by perineal, vaginal and cervical tearings. This finding is found in the Open Journal of Obstetrics and Gynecology literature; however our prevalence of tearins is slightly higher than those reported in other studies [11]- [16]. These complications are generally related to a poor appreciation of dilation, with forceps being applied while cervical dilation is incomplete.…”
Section: Maternal Prognosissupporting
confidence: 52%
“…Dans notre série, un nouveau-né avait un score d'Apgar inférieur sept à cinq minutes de vie après extraction par ventouse mais sans aucune différence entre les deux groupes, ce résultat a été également retrouvé dans la comparaison forceps-ventouse dans la méta-analyse de Johanson et al [23] Le taux de transfert en réanimation néonatale était de 4,3 % dans le groupe ventouse et de 8,7 % dans le groupe spatules mais sans différence significative, ces données sont comparables aux données de la littérature [25,26]. Ces taux de transfert sont le résultat des indications même des extractions instrumentales.…”
Section: Discussionunclassified